Use of Spanish Broom (Spartium junceum L.) Fibers for Removal of Heavy Metal Ions from Aqueous Solutions. Issue 1 (2nd January 2016) - Cerchiara, T.; Chidichimo, A.; Aloise, A.; Chidichimo, G.
Abstract : In this work, potential use of Spanish broom fibers for removing from aqueous solutions heavy metal ions such as copper Cu(II) and lead Pb(II) was investigated. The fibers were extracted by DiCoDe (Digestion-Compression-Decompression) process changing experimental conditions. Morphology of fibers was evaluated by scanning electron microscopy and chemical composition, as well as the carboxylic group content, was determined by conventional methods. Various initial concentrations of heavy metal ions were studied to explore potential sorption on cellulose fibers. The results suggest that cellulose fibers, extracted by different conditions of DiCoDe process, are capable of sorbing metal ions.